Step-by-step explanation:
Notice the vertex and focus have the same y coordinate so this means we will have sideways parabola.
Equation of a sideways parabola is
[tex](y - k) {}^{2} = 4p(x - h)[/tex]
Since the vertex is (0,0), we can get rid of h and k.
[tex] {y}^{2} = 4px[/tex]
Next Section: Value of P:
The value of P is the displacement between the focus and vertex.
So we do
[tex]p = x _{focus} - x _{vertex}[/tex]
[tex] p = - 6 - 0[/tex]
[tex]p = - 6[/tex]
[tex] {y}^{2} = 4( - 6)x[/tex]
[tex] {y}^{2} = - 24x[/tex]
or
[tex] - \frac{ {y}^{2} }{24} = x[/tex]